Recommendations from the Expert Meeting «Secondary progressive multiple sclerosis: unresolved issues and prospects» - N. V. Khachanova; A. N. Boyko; K. Z. Bakhtiyarova; Ya. V. Vlasov; E. P. Evdoshenko; S. A. Sivertseva; T. E. Schmidt; M. V. Shumilina (Неврология, нейропсихиатрия, психосоматика)
The meeting of experts discussed the clinical and pathophysiological features of secondary progressive multiple sclerosis (MS) (SPMS), clinical trials, and promising treatments for the progressive MS stage, as well as proposals contributing to the improvement of the current state of the problem of SPMS. In particular, the definition of and criteria for SPMS are formulated; the earliest period, when its confirmed progression can be recorded, is stated to be 3 months. The exacerbation-unaffected disability progression confirmed 6 months later may be considered to be more convincing. The introduction of tools for the early assessment of disability progression into routine practice will be able to identify the signs of progression at an earlier stage in order to timely change treatment policy. It is also noted that therapeutic possibilities in establishing secondary progression, especially in the absence of exacerbations, but in maintaining progression, are still insufficient. Certain hopes for slowing the progression in patients with SPMS are associated with the advent of siponimod, a new molecular class of S1P receptor modulators. The confirmed efficiency of siponimod in a large population of patients with SPMS allows the latter to be recommended for its treatment with both persistent disease activity (SPMS with exacerbations) and disability progression without exacerbations (SPMS without exacerbations).